Pathologic evaluation of the solid variant of aneurysmal bone cysts with USP6 rearrangement with an emphasis on the frequent diagnostic pitfalls. Issue 8 (27th April 2020) - Zhou, Jun; Zheng, Saifang; Zhou, Luting; Yong, Xiang; Zhang, Yanping; QinXia,; Zhang, Wenjing; Wang, Chaofu
Abstract : The solid variant of aneurysmal bone cyst (SVABC) is very uncommon and frequently misdiagnosed. We reevaluated and summarized the clinicopathologic features of 17 SVABCs and further discussed the use of this nomenclature to differ SVABCs from extragnathic giant cell reparative granuloma (GCRG) in the setting of the USP6 rearrangement era. The immunohistochemical markers included α‐SMA, SATB2, AE1/AE3, Ki67, S100, CD68 and P63. USP‐6 status was detected by fluorescence in situ hybridization using a break‐apart probe. The 17 patients with SVABCs comprised 10 males and 7 females ranging in age from 4 to 70 years. The involved locations included the long bone (n = 11), hand (n = 4), rib (n = 1) and vertebra (n = 1). The lesions were characterized by proliferated spindle cells with scattered giant cells and hemorrhages with variable positive α‐SMA, SATB2, CD68 and Ki‐67 expression. All patients had USP6 rearrangements without H3F3A glycine 34 mutations. Our study reveals that SVABC shares similar clinical and histologic features with other bone lesions, which may lead to an erroneous diagnosis. The presence of an USP‐6 rearrangement contributes to the diagnosis SVABC; SVABC and most of the previously documented extragnathic GCRGs may be considered within the umbrella of primary aneurysmal bone cysts.